Acolhimento educacional de alunos com deficiência no ensino de Ciências e Biologia na escola de Educação Básica: um estudo do tipo mapeamento - Santos, Gabriela Contin dos (Universidade Federal de São Carlos, 2023)
The general objective of this work is to address the reception of students with disabilities in Science and Biology Teaching in Basic Education, based on the mapping of dissertations and theses. For the composition of the corpus of analysis of this work, we used, as database, the Brazilian Digital Library of Theses and Dissertations (DLTD). For the construction and development of this study, a qualitative methodology was chosen, considering the execution of a Systematic Mapping of the selected academic productions, as well as the contributions of Falbo (2018) and Vosgerau and Romanovski (2014), providing the composition of the corpus of analysis and production of results. Twelve articles published by DLTD were analyzed. The mapping of academic productions was carried out by reading and recording these works, which were chosen based on inclusion and exclusion criteria and segmented according to the theme addressed by each one. At first, they were divided into three groups that deal with the deficiencies worked on by the selected texts, namely intellectual and mental disabilities, visual disabilities, and students with disabilities in general. Subsequently, the dissertations were analyzed based on their general objectives, with which it was possible to gather them into three topics based on the theme discussed by the theses, namely “Conception and perception of the teacher in relation to the student with a disability”, “Importance of using pedagogical practices and resources for teaching students with disabilities” and “Other topics”. The analyzed academic productions point to the importance of educational reception for the teaching-learning of students with disabilities and how this reception facilitates interpersonal interactions and helps in the development of effective educational practices. They also show the need for continuing education for teachers, as it is through this knowledge that educators can produce pedagogical resources adapted for students with disabilities. About reception in the teaching of Science and Biology, only one thesis was found and with it is concluded that it is necessary to bring to the teaching of Biology practices that involve and benefit the student with disability, but that also include the student without disabilities and provide welcome for these groups of students, favoring teaching and learning on an equal basis for everyone.
Educational support for students with disabilities in the teaching of Science and Biology in Basic Education schools: a mapping study Mathematical education
Keywords: Acolhimento Educacional; Alunos com Deficiência; Ensino de Biologia; Ensino-Aprendizado; Educational Reception; Disabled Students; Biology Teaching; Teaching-Learning; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO